Branding Brazilian slums through 'freeware' cultural production: the case of Rio de Janeiro - Antonio Russo (European Regional Science Association (ERSA), 2012)
This paper reflects on a "cultural industry model" with important potential for local development, which is the network of independent cultural producers of Brazilian slums. The landscape of favelas is unique: plagued by poverty and crime, they have come to encapsulate the worst aspects of chaotic urban growth in Latin American cities, and are consequently reified as spaces violating the "social norms" of sustainable urban development. Maybe more in Rio de Janeiro than in any other Brazilian or Latin-American cities, favelas are nevertheless important components of an urban cultural landscape of outstanding value, but just as difficult to conceptualise. They are also a unique form of informal urbanisation, and – as pointed out by a critical current of political scientists – they have affirmed as spaces of social emancipation and resistance. Recognising the social value of Rio's favelas brings us to explore the way in which they have been developing as spaces of creative expression, according to a peculiar model anchored on freeware and hacker culture, and receiving the support of the federal government's cultural policy. This model made a remarkable change in the way they came to be "legitimised" by the metropolitan society above the criminalising discourses of mainstream commercial media. The free cultural products of favelas promote community pride, recognition and visibility, and ultimately inclusion, but also job creation in its peculiar consumption filiere, especially when the potential as "tourist brand" is taken into account. For this reason, short-circuiting a "creative" creative industry development policy, UNESCO's landscape protection strategy, and the (increasingly ambitious) Rio de Janeiro agenda of tourism development and place marketing, has become of paramount importance for making a giant step out of the poverty issue, and in this sense Rio could serve as a template for the whole Latin American continent, to say the least.
Keywords: Z10; Z13; R30; 330; Creative production; hackerism; slums; urban development; tourism; branding